Oral Narratives of the Oka Tradition in Wewewa, Southwest Sumba: An Ethnopedagogical Study - Kanisius Kami; I Wayan Suastra; Ida Bagus Putu Arnyana (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to describe Oka oral speech of Wewewa community through ethnopedagogical point of view. The research design used is descriptive qualitative. Data were obtained from the oral speech of Oka of Wewewa community as well as used as the object of research. The object of this research is the ethnopedagogical value of Oka oral speech. Primary data sources are Oka oral tradition speech. This primary data source is obtained from the speakers/customary elders who speak the Oka oral tradition. Primary data sources were also obtained and collected by researchers from Wewewa community members based on interviews. While secondary data sources are obtained by researchers from documents directly related to the Oka oral tradition. The instrument of this research is the researcher himself. The data collection method of this research is through observation, interviews, and documentation studies. Data analysis techniques are data transcription, gloss translation of data, data selection, data identification, data classification, and analyzing and interpreting data so that it can be reported in the data discussion section. Based on the results of the study, the researcher concluded that in Oka's oral tradition speech, ethnopedagogical values that are manifested in Oka's oral tradition speech include respect for ancestors, hard work, repentance of lost children, togetherness, gratitude, and kinship.